Penelitian Umkm: Analisis Keunggulan Dan Strategi Pemasaran Pada 'Seblak Teh Windy’ - Rakhman, Arif; Maula, Kholida Atiyatul; Kristina, Kristina; Natalia, Ovia; Rachmasari, Ananda Putri; Puspariani, Wini; Ayumi, Shafira Mega; Febriana, Ellyza; Kowiyah, Elita (Jurnal Ilmiah Wahana Pendidikan, 2024)
This report documents the results of an interview with the owner of the micro, small, and medium-sized enterprise (MSME) "Seblak Teh Windy." As a producer of traditional Indonesian cuisine, Seblak Teh Windy introduces a unique innovation by combining the flavors of seblak, a traditional dish from Bandung, with a special touch of tea. The interview was conducted to gain a deeper understanding of the business journey, marketing strategies, challenges faced, and the contribution of Seblak Teh Windy to the local community. The results of the interview highlight the crucial role of MSMEs in supporting the local economy and preserving local wisdom through innovative culinary products. As a successful venture, Seblak Teh Windy serves as an inspiration for other MSMEs to continue growing and innovating in response to market dynamics. This report provides a holistic overview of Seblak Teh Windy's contribution to supporting the growth of MSMEs and sustaining Indonesia's culinary heritage.